The Use of Teaching Biomodels in Veterinary Sciences: Review - Balaguera Quinche, David Fernando (2021)
Didactic models have been used throughout many years as a means for understanding human and animal medicine, especially in subjects such as anatomy, physiology, surgery, and pathology that are central to the training of the medical professional. These models are three-dimensional artificial models that seek an approximation to the morphology and function of an organism, help its exploration and, if possible, a replacement to reduce practices with animal experimentation. This literature review was constructed by searching different sources, and the authors’ own didactic exercises will also be presented to highlight some important aspects of the use of didactic biomodels from different disciplines of veterinary medicine and also different points of view for their implementation as a tool to promote the teaching-learning process in students.